Taxanes in adjuvant and neoadjuvant therapy for breast cancer - S. V. Limareva (Опухоли женской репродуктивной системы)
Taxanes (paclitaxel and docetaxel) are currently considered to be basic cytostatics in the treatment of all breast cancer (BC) stages. The results of conducted and ongoing clinical trials suggest that incorporation of taxanes into adjuvant and neoadjuvant chemotherapy regimens enhances the efficiency of treatment for operable BC and show it necessary to apply an individual approach depending on prognostic and predictive factors.